Myelin Dynamics Throughout Life: An Ever-Changing Landscape? - Williamson, Jill M.; Lyons, David A. (Frontiers in Cellular Neuroscience, 2018)
Myelin sheaths speed up impulse propagation along the axons of neurons without the need for increasing axon diameter. Subsequently, myelin (which is made by oligodendrocytes in the central nervous system) allows for highly complex yet compact circuitry. Cognitive processes such as learning require central nervous system plasticity throughout life, and much research has focused on the role of neuronal, in particular synaptic, plasticity as a means of altering circuit function. An increasing body of evidence suggests that myelin may also play a role in circuit plasticity and that myelin may be an adaptable structure which could be altered to regulate experience and learning. However, the precise dynamics of myelination throughout life remain unclear – does the production of new myelin require the differentiation of new oligodendrocytes, and/or can existing myelin be remodelled dynamically over time? Here we review recent evidence for both de novo myelination and myelin remodelling from pioneering longitudinal studies of myelin dynamics in vivo, and discuss what remains to be done in order to fully understand how dynamic regulation of myelin affects lifelong circuit function.